THE MAINTENANCE OF MINANG LANGUAGE BY MINANG’S FAMILY IN KOTAMATSUM II MEDAN - Yenita Uswar (Universitas Potensi Utama, 2018)
The objectives of this qualitative research were (1) to identify the factors that affect the maintenance of Minang language (ML) in Kotamatsum II Medan, (2) to discover the parents’ efforts in maintaining ML in Kotamatsum II Medan and (3) to find out the reason why the speakers have to maintain ML. The population is the Minang’s people in Kotamatsum II Medan. The sample was 10 families including 10 parents and their children. The research sees to investigate the language maintenance both parents and children by Minang’s families in Kotamatsum II Medan. After distributing questionnaire and did some interviews it is found that Minang’s families in Kotamatsum II Medan especially for the third generation (children) had the danger level in ML when they communicated to each other. Meanwhile, the data analysis also showed that both fathers and mothers communicated to each other with ML but when they communicated to their children sometimes they mixed between Indonesia and Minang Language. This condition occurred because of the influence of the environment